Evaluation Of Serum Magnesium, Calcium and Phosphorus in Female Patients Diagnosed with Menstrual Disorders - Sharma, Khushbu; Fiza, Bushra; Mathur, Shikha (Journal of Neonatal Surgery, 2025)
Introduction: Every healthy woman after attaining puberty undergo hormonal changes, go through menstruation cycle every month which involves the coordination of many events by the hypothalamus, pituitary, ovarian axis and is readily influenced by physiological, pathological and psychological changes occurring during the reproductive lifespan. They suffer from various menstrual disorders and their proper nutritional management is necessary. Levels of Serum Magnesium, Calcium and phosphorus may play important role in symptoms of these disorders. Aim: To evaluate the levels of serum Magnesium, Calcium and Phosphorus levels among female patients diagnosed with menstrual disorders. Material and Method: In the present case control study, serum Magnesium, Calcium and Phosphorus levels were determined in 100 Female Patient’s diagnosed for menstrual disorders i.e Abnormal uterine bleeding or AUB, PCOS and Dysmenorrhea, visiting the outpatient department (OPD) of gynecology fulfilling the inclusion criteria and exclusion criteria were enrolled for the study. Healthy females with a regular menstrual cycle constituted the control group. Inclusion criteria for the study were Females who were suffering from Abnormal uterine bleeding (AUB), Polycystic ovary syndrome (PCOS) and Dysmenorrhea between 18- 45 years of age and who were interested in taking part in the study. Females with Age below 18 and above 45 years, who are on drugs or hormone therapy, had an IUCD (intrauterine contraceptive device) were known to have cervical or uterine malignancy, fibromyoma etc. and Pregnant women were excluded from the study. Blood samples were collected by venipuncture using standard aseptic technique and following investigation were performed. Serum Calcium, Magnesium, Phosphorus by potentiometry using micro slide assay method on VITROS 5600. Result: A total of 100 females diagnosed with Polycystic Ovary Syndrome (PCOS), Dysmenorrhea, and Abnormal Uterine Bleeding (AUB) were included in the study. The mean age was comparable between the control and patient groups for AUB and Dysmenorrhea, while the PCOS group had a relatively lower mean age (23.63 ± 4.50 years). The mean serum calcium level was 8.40 ± 1.76 mg/dL in the AUB group (P = 0.002), 8.23 ± 1.55 mg/dL in the PCOS group (P < 0.001), and 8.75 ± 1.72 mg/dL in the Dysmenorrhea group, with overall statistical significance (P = 0.063). The mean serum magnesium level was 2.61 ± 1.02 mg/dL in the AUB group (P < 0.001), 2.33 ± 0.82 mg/dL in the PCOS group (P < 0.001), and 2.88 ± 1.07 mg/dL in the Dysmenorrhea group (P < 0.001). Mean serum phosphorus levels were 5.28 ± 1.39 mg/dL in the AUB group (P < 0.001), 5.43 ± 1.64 mg/dL in the PCOS group (P < 0.001), and 5.21 ± 1.54 mg/dL in the Dysmenorrhea group (P < 0.001) . Conclusion: Levels of Calcium, phosphorus and Magnesium play a vital role in muscle function and hormonal regulation. They both play important role in healthy menstrual cycle. Imbalance of these minerals could contribute to menstrual abnormalities. Mean Calcium level was found to be decreased in patients with menstrual disorders whereas Mean Phosphorus levels and Magnesium levels increased in patient with menstrual disorders.